Correlates of Adoption of Cotton Cultivation Practices - Umesh R. Chinchmalatpure; V. V. Mayani (Journal of Agricultural Extension Management, 2025)
Cotton is one of the most important commercial cash crops in our country. It is also the major crop cultivated in the rehabilitated area of Baroda district of Gujarat by the Project Affected Farmers (PAFs). However, the PAFs have not yet increased their agricultural income because they are not aware about modern agricultural technology. Therefore the .Sardar Sarovar Narmada Nigam Limited, Baroda has been providing them technical guidance as well as supplying the improved seed/variety of different crops. It is observed that the farmers do not adopt the recommended cotton cultivation practices fully, due to various reasons, even though the production per unit area is low. The process of acquisition of knowledge and adoption of recommended practices by the PAFs depends on their profile constituted by various socio-personal, economic, communicational and psychological characteristics. The present study was therefore conducted in order to analyse the influence of various socio-personal, economic, communicational and psychological characteristics of the PAFs on adoption of recommended cotton cultivation practices